Efficacy and Accuracy of Non-Biopsy Serological Diagnosis in Celiac Disease: A Meta-Analysis of Recent Advances - Al Abdulqader, Abdulrhman Khaled (Journal of Neonatal Surgery, 2025)
Background: Celiac disease (CD) is traditionally diagnosed via duodenal biopsy, but advances in serological testing—particularly anti-tissue transglutaminase IgA (tTG-IgA) and endomysial antibodies (EMA)—have prompted a shift toward non-biopsy diagnostic protocols, especially in pediatric settings. However, questions remain about the reliability and generalizability of these strategies across populations. Objective: To evaluate the pooled diagnostic accuracy of non-biopsy serological tests for celiac disease compared to biopsy-confirmed diagnosis, and to assess consistency across different serological thresholds, populations, and testing platforms. Methods: A systematic search was conducted across five databases to identify studies evaluating the diagnostic performance of tTG-IgA, EMA, or DGP serological markers against duodenal biopsy. Data from 12 eligible studies were pooled using a random-effects model. Primary outcomes included sensitivity, specificity, and overall effect size. Heterogeneity and publication bias were assessed using I² statistics, Egger’s regression, and funnel plots. Results: The meta-analysis yielded a pooled effect size of 0.889 (SE = 0.105; 95% CI: 0.682–1.095), indicating strong diagnostic accuracy for non-biopsy serological testing. Heterogeneity was negligible (I² = 0%, Tau² = 0), suggesting consistency across studies. The Fail-safe N was 291 (p < .001), and Egger’s test showed no significant publication bias (p = 0.340). Serological thresholds ≥10× upper limit of normal for tTG-IgA, especially when combined with EMA or DGP positivity, yielded near-perfect predictive values for biopsy-confirmed celiac disease in both pediatric and selected adult populations. Conclusions: Non-biopsy serological diagnosis—particularly tTG-IgA ≥10× ULN confirmed with EMA or DGP—demonstrates high diagnostic accuracy and reliability in diagnosing celiac disease. These findings support expanding biopsy-sparing diagnostic protocols beyond pediatrics under defined clinical conditions